PENGARUH MEKANISME GOOD CORPORATE GOVERNANCE, LEVERAGE, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA: Studi Empiris pada Perusahaan Kategori Indeks Sri-Kehati yang Terdaftar dalam Bursa Efek Indonesia Periode 2013-2017 - Wilson; Arihadi Prasetyo (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2020)
The Aim of this research is to determine empirically the impact of good corporate governance mechanism (institusional ownership, managerial ownership, audit committee), leverage, size on earnings management. The Sample on this research consisted of 14 companies listed in the Indonesia Stock Exchange in 2013-2017, categorized index Sri-Kehati whiches comprises 70 unit samples observed. The research evidence that the exsitence of institutional ownership, audit committee decrease earning management, also the more size of firm the more decrease earnings management. While higher leverage magnitude earnings management. Managerial ownership on the other has no on impact on earnings management. Keywords: good corporate governance, leverage, size, and earning management